Impactos ambientais e na saúde pública das águas de abastecimento no Município de Aracati-CE - Sousa, Joyce Shantala Fernandes de Oliveira (2023)
The effects on surface and groundwater quality have an impact on the population's quality of life since prolonged and excessive consumption of contaminated water can harm people's health. The work was done in the municipality of Aracati, which is situated on the east coast of the State of Ceará, in the Northeast Region of Brazil, with the goal of examining the vulnerability and risk that includes all pertinent data to the Medical Geology research conducted in the municipality to identify potential areas of groundwater contamination and its effects on health. 25 water samples, including those from surface and groundwater springs, were taken in October 2020, and the primary sources of pollution were catalogued. To determine the relationship between the various existing variables and the pollutant sources found in the area, the data were processed using ionic classification, statistical analysis, interpolation techniques in the Geographic Information System (GIS) environment, ionic ratio, and the framing of waters in Ordinance Nº 888/2021 of the Ministry of Health. The data interpretation shows that 82% of the study area exhibits medium to high natural vulnerability; the Jaguaribe River is categorized as saline water; the waters have a slightly acidic character between 4.26 and 7.68; sodium chloride waters predominate (95%); and the waters have a hydrochemical pattern resembling water with saline intrusion, which is confirmed by correlations observed among the parameters in the statistical analysis. 60% of the samples are brackish waters (average STD concentration: 1587.67 mg/L); 50% of the samples have nitrate concentrations that are higher than those permitted by law (average: 13.21 mg/L). It was discovered that all 20 groundwater samples had at least one parameter that was below the standard for potability. These parameters may have been caused by geological or human activity, and the research area's lower elevation may have contributed to the change in water quality. The carciniculture effluent present has a conductivity value that is 20 times higher than what is permitted by COEMA Resolution Nº 9/2021. With the information provided above, it is clear that the people of Aracati are subject to environmental effects and health concerns, and the accountable parties need to be worried about the current situation.